Tc-99m Tetrofosmin Scintimammography for the Detection of Recurrent Breast Cancer in a Patient with Equivocal Mammography Study - Samir Hussein; Sukhpal Sawhney; Adil Al-Jarrah (Sultan Qaboos University Medical Journal, 2008)
This is a case report describing a patient at Sultan Qaboos University Hospital, Oman, with recurrent local breast cancer and axillary lymph node metastasis. The cancer was detected with 99Tc-m tetrofosmin scintimammography after an equivocal mammography study.